The Influence of Profitabilities and Capital Structure to Company Performance - Louvisa, Dina Esra; Tarigan, Lukas; Sembiring, Carolina F. (Universitas Kristen Indonesia, 2017)
The influence of profitabilities and capital stucture to company performance. Research aims at explaning effect of profitability and capital stucture on company performance. Research also considers testing the effect of profitability and capital stucture simultaneously or partially on company performance. Study sample of 7 property and real estate companies listed on the Indonesia Stock Exchange. Observation made during the period of 7 years, the years 2009-2015. Data analysis techniques used in the study was conducted using miltiple regression analysis. Results of research indicate that variables of profitability and capital structure simultaneoously provide significant effect on company performance. Partially, only variabel of profitability ROE significantly affect company performance, while ROA not. Also DER variable of Capital Structure don’t have significant affect on company performance.Keywords: Profitability, Capital Structure, Company Performance